Comparative evaluation of postpartum versus post MTP insertion of intrauterine contraceptive device - Gutgutia, Isha; Rani, Kumari Usha; Prateek, Shashi; Arora, Renu; ., Shubham (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was planned to evaluate acceptability, safety and continuation rate of postpartum intrauterine contraceptive device (PPIUCD) and to compare it with well accepted post MTP IUCD in Indian population. Methods: This was a prospective study conducted in VMMC and Safdarjang Hospital, New Delhi, India. Copper T 380-A was inserted in 100 woman in postpartum period and in 100 woman in post MTP period. Follow up done at 6 weeks, 3 months and 6 months. Safety was assessed in terms of expulsion, IUCD failure/pregnancy rate, perforation, removal of IUCD, visibility of strings and various complain at each visit. Continuation rate along with their level of satisfaction was compared at the end of 6 months. SPSS software, Chi-square test and student T test were used for analyzing the results. P value ≤0.05 considered as significant. Results: Acceptance of post MTP IUCD was more than PPIUCD. There was statistically no significant difference in expulsion rate, removal of IUCD and various complaints. There was no case of perforation in either group. Non visibility of strings was major cause of concern and apprehension in PPIUCD group. Only one case of pregnancy was reported in PPIUCD group while no failure was reported in post MTP group. Continuation rate and level of satisfaction were comparable in both groups. Conclusions: PPIUCD is equally safe and effective as post MTP IUCD.